Millenial E- Learning Systems and Their Academic Performance in Mathematics - Rizada, Ma Chona S; Rey, Raymond P (American Journal of Multidisciplinary Research and Innovation, 2023)
This paper uses digital and technologically enhanced learning processes to present the millennial generation’s E-learning systems in mathematics courses, attitudes, and academic performance. It aims to determine the e-learning systems of college students in their mathematics classes and their effects on their academic performance. This study used qualitative and quantitative methods and descriptive–correlational and descriptive-comparative research methods involving 72 college students taking p mathematics courses. The results show that regarding e-learning materials, the majority strongly agreed with preferred using Technologies to solve problems using application software, web assignments submitted on yahoo chat, emails, messengers, and solving problems in class using a calculator’s math lab and math way. Millennial e-learners prefer Online based learning, Video conferencing, yahoo groups, group chats, messengers’ groups, video calls, emails, Twitter, Instagram, Math software, and online chat. Students’ academic performance improved when the e-learning system was used, and it was found that their academic grades differed significantly when e-learning systems over traditional learning systems. The E-learning style is recommended in teaching mathematics courses.